IDENTIFICATION OF THE RELEVANT STAKEHOLDER GROUPS - THE FIRST STEP TO THE STRATEGIC STAKEHOLDER MANAGEMENT IN AGRICULTURAL HIGHER EDUCATION - A STUDY CASE IN THE REPUBLIC OF MOLDOVA - Veronica PRISACARU; Tatiana SEVCIUC (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The growing competition in the market of educational services requires increased efforts to ensure an adequate quality of the educational products offered by vocational education institutions. However, reaching the adequate quality standards is impossible without the active involvement of stakeholders. Only through the synergy of the efforts of all groups of stakeholders, the progress in the quality of educational services provided can be achieved - a particularly important task especially for agricultural vocational education, which has a strategic significance for the Republic of Moldova. Knowing and correctly perceiving their role in this regard is required as an indispensable factor of quality and performance. The basic objectives of the research were: a) mapping the stakeholders of the State Agrarian University of Moldova; b) evaluation of the stakeholders' perception by the management team and the university staff. In order to achieve these objectives, the following research tools were used: the synthesis of a series of scientific publications with reference to the emergence and evolution of stakeholder theory in higher education; mapping process; structured thematic interview; tabular and graphical presentation of the primary data; structural analysis; descriptive method. As a result of the research, the mapping of the stakeholders of the State Agrarian University of Moldova was performed. Also, the areas that require intervention in the quality of stakeholder perception by university managers and teaching staff were identified: more active promotion of the value of stakeholders; increasing the level of involvement of the teaching staff in collaborative activities with external stakeholders.